THE HISTORY OF HADRAMI ARABIC COMMUNITY DEVELOPMENT IN SOUTHEAST ASIA - Subchi, Imam (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
The Arab community has an important role in the process of Islamization in Southeast Asian. One of the Arab community that played an important role in the spread of Islam in Southeast Asia was merchant who came from the south of the Arab lands. This paper examines the development of the Hadrami Arab community in Southeast Asia. Using authoritative studies of literature, this paper discusses the development and revival, and the roleplayed by the Hadrami Arab community in several fields such as economics, education, Islamic da?wah and politics in the 18th to 20th centuries. The method used by the Hadrami Arab community in the process of Islamization is by peaceful means, respect for locality, thus facilitating the process of adaptation and reciprocity of the local population in the Southeast Asian.